Social Media and Symbolic Interactionism in the #KaburAjaDulu Movement on TikTok - Sejati, Mahyeksi Suci; Istikomah, Ayu; Setiawan, Agnes; Dwifano, Hilal; Pratiwi, Sintia Diah; Rohim, Ridwan Nur (Journal of Media and Digital Society on SDGs, 2025)
The hashtag #KaburAjaDulu went viral among young Indonesians in response to work pressures, with 173.9K posts on TikTok. This phenomenon influences the perspectives of the younger generation who want to move forward and develop, not just stay silent in the face of the country's situation. This descriptive qualitative research analyzes the phenomenon through observation and daily TikTok content analysis. The results show that this hashtag is an expression of disappointment as well as a reflection of the desire to develop outside a system that is not yet ideal. Although considered less nationalistic, many see it as a strategy to gain skills to later contribute back to Indonesia. Keywords: Society, Media, Hashtag, Tiktok, #KaburAjaDulu